Stock Market Volatility during Rumours of War and Actual War: Case of Russia-Ukraine Conflict - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2022)
Investors are humans and are sensitive to rumours of war and actual war events, which appear to have different impacts on stock market performance. Objective: this paper evaluates a two-stage differential effect of the current Russian invasion in Ukraine on stock market volatility in EU, UK and US stock markets. Prior work: the paper inclines on prior works on the effect of international conflicts on stock markets. Method: the paper uses stock market data for EU, US and UK for 21 days before Russian troop build-up on Ukraine boarders in 2021 and 21 days during the troop build. It also collected 21 days stock market data for 21 days in 2022 before Russian invasion in Ukraine and for 21 days during the Russian invasion. Data were analysed using the t-test statistics and line graphs for trends. Finding: results show that Russian invasion in Ukraine has significantly caused stock market volatility for EU(FTSE EU), UK (FTSE London) and US (S&P500). However, the EU stock market (FTSE EU) has suffered higher volatility compared to UK and US. In the same vein results show that, the US stock market (S&P500) remains the less volatile and safest investment haven to safeguard stocks during the ongoing war in Ukraine. Implication: The results contribute latest stock market investment information to investors and stock market hedgers to make risk and investment decisions in this conflict times. It also offers an important new case study for business economic classes in higher education business schools, and highlights and agenda for further research. Value: the paper contributes a two-stage differential analysis approach (stage 1 troop build-up stage, and stage 2 actual war stage) – and reveals divergent implications of a two stage application and results for stock market analysis.